Socioeconomic Status, Environmental Health Knowledge, and Housewives’ Behavior in Maintaining Healthy Housing at Subsidized Flats in East Jakarta, Indonesia - Dewi, Alfitra Firizkia Luthfiana; Fitria, Laila (Kesmas, 2025)
Healthy behavior among housewives is a crucial aspect of efforts to maintain healthy housing. This study aimed to analyze the relationship of socioeconomic status (e.g., household income, level of education of family head and housewives, and family head’s occupation) and environmental health knowledge with housewives’ behavior (e.g., vector control, waste management, home ventilation, cigarette smoking, and hand sanitation hygiene) in maintaining healthy housing in the subsidized flats in East Jakarta, Indonesia. This cross-sectional study employed the two-proportion hypothesis test formula and a simple random sampling method, recruiting 137 housewives for interviews. Data were analyzed via logistic regression to determine factors related to housewives’ behavior. Analysis demonstrated a significant relationship of housewives’ level of education (OR = 2.883; 95% CI = 1.339−6.209), the family heads’ level of education (OR = 3.856; 95% CI = 1.711−8.690), and housewives’ environmental health knowledge (OR = 2.687; 95% CI = 1.304−5.294) with housewives’ behavior. Multivariate analysis demonstrated that the level of education of family heads and the environmental health knowledge of housewives were the dominant factors influencing housewives’ behavior in maintaining healthy housing. The findings offer useful insights for planning and maintaining flats in other areas, considering the growing number of residents.